FOXD3 confers chemo-sensitivity in ovarian cancer through a miR-335/DAAM1/myosin II axis-dependent mechanism - Shufen Wang; Yan Ma; Yi Hu; Xia Zhao; Yilin Li; Shuming Ouyang; Guifang Luo (BMC, 2023)
Abstract Background Chemotherapy is among the most common treatment methods for ovarian cancer (OC). However, chemoresistance limits the effectiveness of chemotherapy and leads to treatment failure. We herein investigate the biological effect of forkhead box D3 (FOXD3) in the chemoresistance of OC cells. Methods Expression of FOXD3, miR-335 and disheveled-associated activator of morphogenesis 1 (DAAM1) was detected in OC cells and tissues. The regulatory network of FOXD3/miR-335/DAAM1 was validated by dual-luciferase reporter and ChIP assays in vitro. After ectopic expression and depletion experiments in carboplatin/paclitaxel (CP)-resistant (A2780CP) or sensitive (A2780S) OC cells, cell viability, colony formation and apoptosis were tested by CCK-8 assay, colony formation assay and flow cytometry respectively. Effects of FOXD3 on the chemoresistance of OC cells in vivo were evaluated in OC xenografts in nude mice. Results Overexpression of FOXD3 impaired the proliferation and chemoresistance of OC cells, which was related to the promotion of the miR-335 expression. Functionally, DAAM1 was a putative target of miR-335. Silencing of DAAM1 was responsible for the inhibition of myosin II activation, consequently leading to suppressed OC cell proliferation and chemoresistance. In vivo results further showed that FOXD3 weakened the chemoresistance of OC cells to CP. Conclusion Taken together, we unveil a novel FOXD3/miR-335/DAAM1/myosin II axis that regulates the chemoresistance of OC both in vitro and in vivo.